KONDISI PEREMPUAN YANG TEREFLEKSKAN DALAM PUISI WILLIAM BLAKE EARTH’S ANSWER - Triyatun, Novita (LANTERN (Journal on English Language, Culture and Literature), 2012)
This research deals with the situations and conditions happened in England at the end of the seventeenth century especially about domination the man over the woman who was reflected in William Blake’s poem Earth’s Answer. Based on the fact that there are relations between history and literary, this thesis analyzes the domination the man over the woman who was reflected in William Blake’s poem Earth’s Answer. The aim of this research is to understand the poem of William Blake. Besides understanding the poem, this thesis also tries to analyze social problem about domination the man over the woman reflected in William Blake poem. The writer not only uses the library research methode but also structural approach. By using the library research method, the writer gets much information as the reference of writing this thesis. Whereas, by using structural approach the writer could understand the poem supported by history of England at the end of the seventeenth century. The result of this analysis is that focussed on the domination the man over the woman that happened in England as the result of the revolution of industry. This condition became more serious as the result of the slavery and prostitution of the woman.